Your Clean Graphene is Still Not Clean - Ondrej Dyck; Aisha Okmi; Kai Xiao; Sidong Lei; Andrew R. Lupini; Stephen Jesse (Advanced Materials Interfaces)
Abstract Researchers working with thin samples, such as monolayer graphene, are consistently struggling against contamination. Indeed, the problem of hydrocarbon contamination is known from the earliest days of electron microscopy and efforts to reduce this problem are ubiquitous to almost all high‐vacuum experiments. Accurate knowledge of the behavior of such contamination is essential for electron beam (e‐beam) based atomic fabrication, where it is aspired to select and control matter on an atom‐by‐atom basis. Here, the vexing question of hydrocarbon contamination on graphene is taken up. Image intensity is used to directly reveal the presence of diffusing hydrocarbons on ostensibly clean graphene. These diffusing hydrocarbons are previously inferred but not directly observed. Surprising dynamic variations of the concentration of these hydrocarbons impels questions about their origin. Here, some possible explanations are presented and some tentative conclusions are drawn. This work updates the conceptual model of “clean graphene” and offers refinements to the description of e‐beam induced hydrocarbon deposition.